Obestatin/Ghrelin Ratio as a New Activity Index in Ulcerative Colitis: Obestatin/Ghrelin Ratio: an Activity Index in UC - Mohammed, Mohammed Amin; Omar, Nesreen Moustafa (International Journal of Innovative Research in Medical Science, 2019)
Background and Aim: Ulcerative colitis (UC) is an immune-mediated systemic inflammatory process that destroys the intestinal mucosa. Ghrelin, an appetite-regulatory hormone, has anti-inflammatory effects including a decrease in circulating cytokines. Some reports demonstrated a strong relationship between the serum ghrelin level and the severity of mucosal inflammation in the gastrointestinal tract. The aim is to investigate serum levels and colonic mucosal mRNA expression of ghrelin, obestatin, and obestatin/ghrelin ratio in patients with UC and to determine their potential as markers for UC disease activity. Patients and Methods: seventy-five outpatients with UC and 45 age- and sex-matched healthy volunteers were enrolled in this study after written conscious consent and approval by the Institutional Review Board of Mansoura University. UC was diagnosed by conventional clinical, radiological, endoscopic, and histopathological criteria. Serum ghrelin, obestatin levels, and their mucosal mRNA expression were measured by ELISA kits and a real-time quantitative reverse transcriptase polymerase chain reaction according to the manufacturer’s protocols. Results: Serum levels and mucosal mRNA expression of ghrelin were significantly higher in patients with active UC than patients in remission p˂0.0001). Obestatin/ghrelin ratio was significantly lower in patients with active UC (0.26±0.08) than those in remission (0.523±0.16; p˂0.0001). Obestatin/ghrelin ratio was negatively and significantly correlated with inflammation and endoscopic scores, colitis activity index, serum ghrelin level, and its mucosal mRNA expression (p˂0.05). Conclusion: obestatin/ghrelin ratio might be a reliable surrogate non-invasive marker of disease activity in UC with significantly high sensitivity, specificity, predictive values, and diagnostic accuracy.